2015
DOI: 10.1007/s00710-015-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the P-12 K-Ti-richterite diopside olivine lamproite from Wajrakarur, Andhra Pradesh, India: implications for subduction-related magmatism in eastern India

Abstract: The P-12 Bpara-kimberlite^from Wajrakarur consists of forsteritic olivine, Al-Na-poor diopside, Fe-Tirich, Al-poor phlogopite, K-Ti-richterite, spinel, perovskite, cymrite, apatite, barite, Ba-Sr-bearing calcite, gittinsite, witherite, strontianite, and hydrogrossular (hydrogarnet). The rock also contains small clasts consisting dominantly of calcite, with lesser Ba-Srbearing calcite, cymrite, barite, strontianite, witherite, apatite, and hydrogrossular. Two generations of forsteritic olivine (Fo 80-93 ) cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…The #110 apatite has a slightly higher SO3 concentration (0.01 wt.%-0.17 wt.%) than the #50 apatite (0.01 wt.%-0.11 wt.%). The F content (#50 apatite: 1.54 wt.%-2.20 wt.%; #110 apatite: 1.75 wt.%-3.26 wt.%) reported in this study is slightly lower than that previously reported for apatite in lamproite (2.09 wt.%-4.83 wt.%) [46,47] and that measured for the apatite in the Mengyin kimberlite (1.95 wt.%-5.67 wt.%) [48]. However, the F content of the apatite is slightly higher than that in other kimberlites.…”
Section: Major Element Characteristicscontrasting
confidence: 82%
“…The #110 apatite has a slightly higher SO3 concentration (0.01 wt.%-0.17 wt.%) than the #50 apatite (0.01 wt.%-0.11 wt.%). The F content (#50 apatite: 1.54 wt.%-2.20 wt.%; #110 apatite: 1.75 wt.%-3.26 wt.%) reported in this study is slightly lower than that previously reported for apatite in lamproite (2.09 wt.%-4.83 wt.%) [46,47] and that measured for the apatite in the Mengyin kimberlite (1.95 wt.%-5.67 wt.%) [48]. However, the F content of the apatite is slightly higher than that in other kimberlites.…”
Section: Major Element Characteristicscontrasting
confidence: 82%
“…Apart from the complexities of their tectonic setting, studies of the petrogenesis of Indian lamproites have been hindered by problems in terminology resulting from resistance to using modern mineralogical-genetic classification schemes and undue reliance upon bulk rock geochemical studies. Many rocks previously described as "kimberlites" have now been reclassified as bona fide lamproites (Fareeduddin and Mitchell 2012;Gurmeet Kaur and Mitchell 2016). The numerous occurrences of "para-kimberlites" have not been investigated using detailed mineralogical studies and are probably varieties of olivine lamproite, e.g.…”
Section: Indian Lamproitesmentioning
confidence: 99%
“…Mesoproterozoic alkaline, potassic, and ultrapotassic intrusive rocks of the Wajrakarur kimberlite field (WKF) occur over an area of ~7,000 km 2 in southern India. Rock types present include kimberlites, orangeites/olivine lamproites, lamprophyres, and carbonatites (e.g., Dongre, Chalapathi Rao, Viljoen, & Lehmann, ; Kaur & Mitchell, ; Smith, Haggerty, Chatterjee, Beard, & Townend, ). Earlier studies focused primarily on the kimberlites and other related rock types basically focusing on their mineralogy, geochemistry, geochronology, and petrogenesis.…”
Section: Introductionmentioning
confidence: 99%